Variability of aerobic abilities of football players during competition season - Novaković P.; Đokić Z. (University Educons, Faculty of Sports and Tourism, Novi Sad, 2012)
The purpose of this study is to determine whether there are differences in VO2max during one season in a team of semi-professional football players. This study will also determine the differences between groups, in relation to their position in the team, as well as in relation between the first team and the reserves. This study was conducted on a male football team, between 16 and 28 years of age and with no health problems, competing in a third-tier league. The technique employed is testing and the instrument is the Shuttle Run test that estimated their aerobic capacity. The testing was conducted indirectly during field tests at the beginning of the preparatory period, at the beginning of the competing period and at the end of the season. After a statistical analysis, it can be concluded that there are significant differences between the initial testing, control testing, and final testing. The initial testing was done at the beginning of the preparatory period and the results of the test ranged from 41.50 to 58.10 ml/kg/min. Then after six weeks, which was also right before the start of the competitive part of the season, the control testing was conducted and the results ranged from 46.90 to 62.30 ml/kg/min. Finally, at the end of the season, after all league matches had been played, the final testing was carried out and the results were obtained ranging from 43.80 to 62.00 ml/kg/min. All the testing was conducted on a sample of 31 players, where no relation was discovered between the status of the players at any of the three time points. However, there were some statistically significant differences from the aspect of the players' position but that is due to the goalkeepers being statistically different from the rest of the team. The cause of the differences in the obtained results are differences in intensity, volume and type of training depending on the stage of the season, as well as the specificity of training for the various positions in the team.